MODEL DINAMIS INVESTASI DI INDONESIA PERIODE TAHUN 2004-2007 - Andini Eka Sulistiowati (Jurnal Ekonomi Pembangunan, 2010)
This research aims to detect national income variable influence, credit rate of interest level and domestic investment previous period towards domestic investment with detects which variable that has influence dominantest towards domestic investment. Method which is used in this researcd is double linear regression PArtisl Adjustement Model used for perceiving short-range and long-range responsivenees from dependent variable to one changed unit of independent variable value. After conducted by t-test known that national income and previous period of the domestic investment individually having influence significantly to the level domestic investment. But credit rate of interest level individually not having influence significantly to the level domestic investment. The influence variable to the level of domestic investment is the level of previous period domestic investment model because analysis model that used is adjustment of partial model. Outside independent variable, in the reality variabel that influencing to the level of domestic investment is national income.